Pretty guardian, Sailor Moon. 11 (New York: Kodansha Comics, 2013)
Just when Usagi thinks things are getting back to normal, she finds that Mamoru is leaving to study abroad in America and Chibi-Usa is returning to the thirtieth century
Keywords: Manga graphic novel